The clinical and genetic features of hereditary pancreatitis in South Australia. Issue 11 (16th May 2022) - Wu, Denghao; Bampton, Tristan J; Scott, Hamish S; Brown, Alex; Kassahn, Karin; Drogemuller, Christopher; De Sousa, Sunita MC; Moore, David; Ha, Thuong; Chen, John WC; Khurana, Sanjeev; Torpy, David J; et al.
Abstract: Objective: To characterise the clinical phenotypes and genetic variants of hereditary pancreatitis in people diagnosed in South Australia. Design, setting, participants: Cross‐sectional study of people who received molecular diagnoses of hereditary pancreatitis from one of four major diagnostic services in South Australia, 1 January 2006 – 30 June 2021. Main outcome measures: Genotypic and clinical features of people with hereditary pancreatitis, including age at onset, attack frequency, pain indices, use of opioid medications, and physical and mental health impact of hereditary pancreatitis. Results: We identified 44 people from ten families who received molecular diagnoses of hereditary pancreatitis during 2006–21 (including 25 Indigenous people [57%] and 27 women [61%]): 36 with PRSS1, five with SPINK1, and three with PRSS1 and SPINK1 mutations (determined by whole exome sequencing). Symptom onset before the age of ten years was reported by 37 people (84%). Pancreatitis‐related pain during the preceding four weeks was described as moderate or high by 35 people (79%); 38 people regularly used opioids (86%). Fifteen patients had diabetes mellitus (34%), and eight had undergone pancreatic surgery (18%). The estimated prevalence of hereditary pancreatitis was 1.1 (95% CI, 0.72–1.4) cases per 100 000 population for non‐Indigenous and 71 (95% CI, 66–77) cases per 100 000 population for Indigenous South Australians. Among people with adult‐onset chronic pancreatitis admitted to South Australian public hospitals during 2001–2019, the proportions of Indigenous people (12%) and women (38%) were smaller than we report for hereditary pancreatitis. Conclusion: The estimated prevalence of hereditary pancreatitis in South Australia is higher than in Europe. PRSS1 gene mutations are important causes, particularly among Indigenous young people.